2009
DOI: 10.1002/jmv.21518
|View full text |Cite
|
Sign up to set email alerts
|

A peptide derived from hepatitis C virus (HCV) core protein inducing cellular responses in patients with HCV with various HLA class IA alleles

Abstract: C35-44 peptide is a well known HLA-A2-restricted CTL epitope originating from hepatitis C virus (HCV) core protein. It was reported that the majority of HCV positive patients had significant levels of serum IgG specific to this peptide. This study addressed whether C35-44 peptide could induce CTL activity restricted to various HLA class IA alleles or could not. This peptide demonstrated binding activity to HLA-A*2402, -A*2601, -A*3101, and -A*3303 molecules, but not to HLA-A*1101 by means of stabilization assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…23 KIRs downregulate cytotoxic T-lymphocyte and NK-cell responses by binding to MHC class I molecules, thereby preventing lysis of target cells. Several epitopes recognized by cytotoxic T lymphocytes are HLA-A11 restricted, including peptides derived from human papillomavirus, 24 hepatitis C virus, 25,26 human immunodeficiency virus, 27e29 and Epstein-Barr virus. 30e32 HLA-DQ5 is associated with a number of autoimmune disorders, such as myasthenia gravis, 33 juvenile rheumatoid arthritis, 34e36 and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…23 KIRs downregulate cytotoxic T-lymphocyte and NK-cell responses by binding to MHC class I molecules, thereby preventing lysis of target cells. Several epitopes recognized by cytotoxic T lymphocytes are HLA-A11 restricted, including peptides derived from human papillomavirus, 24 hepatitis C virus, 25,26 human immunodeficiency virus, 27e29 and Epstein-Barr virus. 30e32 HLA-DQ5 is associated with a number of autoimmune disorders, such as myasthenia gravis, 33 juvenile rheumatoid arthritis, 34e36 and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…( 3,15–17 ) Results from our previous study indicated that a certain few peptides could bind to more than one type of HLA molecule. ( 2,3,18 )…”
Section: Discussionmentioning
confidence: 99%
“…RMA‐S cells (mouse lymphoma cell line deficient in transporter associated with antigen processing [TAP]) were maintained in RPMI‐1640 supplemented with 10% FCS. RMA‐S‐A*2601/human beta‐2‐microglobulin (hb2m) cells were established as described previously ( 2 ) and maintained in RPMI‐1640 supplemented with 10% FCS, 0.75 mg/mL of Geneticin (Calbiochem, Darmstadt, Germany), and 2 μg/mL of Puromycin (Calbiochem).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yutani has reported a phase I study of HCV vaccine in Japanese patients who were either nonresponders to IFN therapy ( n = 23) or had refused treatment ( n = 3). A peptide derived from the HCV core region amino acid residues 35–44 is capable of inducing cellular immune responses in many patients with different HLA class I-A alleles [70]. This peptide was used to develop a series of 6 vaccine injections that enhanced the peptide-specific peripheral CTL activity in 15 out of 25 patients and 12 vaccine injections that augmented peptide-specific IgG production [71].…”
Section: Immunotherapy For Hepatitis Cmentioning
confidence: 99%